2007
DOI: 10.1088/0029-5515/47/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ions dilution and ITG suppression in ASDEX Upgrade ion ITBs

Abstract: Abstract. Internal Transport Barriers (ITBs) in the ion channel in the tokamak ASDEX Upgrade allow for high energy confinement but collapse after only several energy confinement times. In this paper we show that in most cases the ITB phase is terminated clearly before the first ELM burst, thereby ruling out the ELMs as main trigger of the ITB collapse. For the first time, the ITB formation and sustainment are found to be associated with a mechanism of transport suppression based on thermal ions dilution by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 16 publications
5
92
0
1
Order By: Relevance
“…For n α /n e > 1.5%, the amplitude of ITG turbulence, evaluated (in line with the GENE's results) for all components with positive toroidal mode numbers n>20 as |δB r (ITG)| =(Σ n>20 |δB r (n)| decreases significantly when the αsh a v en o ty e tt h e rmalized (time-point T1). This result is consistent with theoretical predictions [32] and experimental observations [33]. For the data taken at the time-point T2, with fully thermalized αs, ITG turbulence has around four times larger amplitudes, decreasing only for n α /n e > 2.8%.…”
Section: -P2supporting
confidence: 91%
“…For n α /n e > 1.5%, the amplitude of ITG turbulence, evaluated (in line with the GENE's results) for all components with positive toroidal mode numbers n>20 as |δB r (ITG)| =(Σ n>20 |δB r (n)| decreases significantly when the αsh a v en o ty e tt h e rmalized (time-point T1). This result is consistent with theoretical predictions [32] and experimental observations [33]. For the data taken at the time-point T2, with fully thermalized αs, ITG turbulence has around four times larger amplitudes, decreasing only for n α /n e > 2.8%.…”
Section: -P2supporting
confidence: 91%
“…We also note that Tardini and his colleagues have similarly linked the formation of an ion transport barrier on the ASDEX-Upgrade tokamak to the suppression of ITG turbulence due to thermal ion dilution by the slowing-down population of fast NBI ions [53]. However, in our GENE simulations we have also included a fastion energy dependence on the ITG stabilization mechanism which is derived from the turbulence measurement, thus differentiating our work from that of [53]. For the data taken at the time-point T2 (maximum value of T e0 , figure 11(b)), the turbulence in the ion-drift direction (positive toroidal mode numbers) has larger amplitudes (by approximately a factor ∼2) and a larger spread (spectra centred around n ∼ 60 with a variance ∼35) than at the time-point T1 (the same T e0 ).…”
Section: Measurements Of the Ion And Electron Drift-wave Turbulence Smentioning
confidence: 78%
“…However, in [28] the role of tracer particles is discussed, whereas with our GENE simulations we have shown that fusion-born αs cannot always be considered as a tracer species. We also note that Tardini and his colleagues have similarly linked the formation of an ion transport barrier on the ASDEX-Upgrade tokamak to the suppression of ITG turbulence due to thermal ion dilution by the slowing-down population of fast NBI ions [53]. However, in our GENE simulations we have also included a fastion energy dependence on the ITG stabilization mechanism which is derived from the turbulence measurement, thus differentiating our work from that of [53].…”
Section: Measurements Of the Ion And Electron Drift-wave Turbulence Smentioning
confidence: 99%
“…One such mechanism is the dilution of the main ion species by the fast ions. In ASDEX Upgrade strong evidence has pointed to a fast ion dilution mechanism for ITB formation at low density [49]. In addition, an increase in local α = β ′ q 2 R due to fast ion suprathermal pressure gradients also stabilises ITG modes through electromagnetic effects.…”
Section: Inclusion Of Fast Particlesmentioning
confidence: 99%